2019
DOI: 10.1039/c9cp03066b
|View full text |Cite
|
Sign up to set email alerts
|

The influence of support materials on the structural and electronic properties of gold nanoparticles – a DFT study

Abstract: This study investigates the effect of commonly used support materials (MgO, C, CeO2) on small gold particles using dispersion corrected density functional theory (DFT-D).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 132 publications
(130 reference statements)
5
41
0
Order By: Relevance
“…36 It was shown that PBE-D3 is in good agreement with the vdW-DF optB88 for the structure of Au clusters. 24 The projector-augmented wave (PAW) formalism 32,37 implemented in VASP was employed to describe the core electrons. A plane-wave kinetic cut-off was set at 500 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…36 It was shown that PBE-D3 is in good agreement with the vdW-DF optB88 for the structure of Au clusters. 24 The projector-augmented wave (PAW) formalism 32,37 implemented in VASP was employed to describe the core electrons. A plane-wave kinetic cut-off was set at 500 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…A Hubbard approach correction (DFT+U) using the method of Liechtenstein et al was used on the Ce 4forbitals. [39][40][41][42][43][44][45] The parameters were set to Ueff = 4 eV (U = 5 eV and J = 1 eV), which better reproduce the reduction of CeO2 as shown in our benchmarking calculations 24 and previous reports. 46,47 Dipole corrections were applied perpendicular to the surfaces upon adsorption of gold clusters.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations